The Learning Process of Small Ball Games in Upper Elementary School Classes in the Bangkunat District - Setiawan, Vitadi; Manullang, Jujur Gunawan; Imansyah, Farizal (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The aim of this study is to understand how the learning process of small ball games is conducted in upper elementary school classes in the Bangkunat District, from the pre-learning stage to the evaluation stage. The design of this research is quantitative descriptive. The subjects of this research are physical education teachers in elementary schools across the Bangkunat District. The data collection technique used in this research is a questionnaire. The questionnaire used is a closed-ended one, where respondents only select answers provided, consisting of 50 items. The data analysis used is descriptive statistics in the form of percentages. The results of the research show that physical education teachers in elementary schools across the Bangkunat District have a “very high” score (57.10%) in program planning. In lesson preparation, they have a “very high” score (71.40%). The implementation of materials has a “very high” score (42.85%). Mastery of materials has a “high” score (71.40%). The teaching methods have a “very high” score (28.60%). The use of facilities and infrastructure has a “very high” score (42.85%). Teaching creativity has a “very high” score (100.00%). The practice of skills has a “very high” score (57.10%). The evaluation of the process and results has a “high” score (42.85%).